2009
DOI: 10.1099/ijs.0.65301-0
|View full text |Cite
|
Sign up to set email alerts
|

Four novel Arthrobacter species isolated from filtration substrate

Abstract: Four Gram-positive, non-motile, non-spore-forming bacterial strains, LC4 T , LC6 T , LC10 T and LC13 T , were isolated from a filtration substrate made from trass, a volcanic rock, and their taxonomic positions were investigated by a polyphasic taxonomic approach. The novel strains grew over a temperature range of 5-40 6C, at pH values of 6-11 and in the presence of 3-7 % (w/v) NaCl. A phylogenetic tree based on 16S rRNA gene sequences showed the novel strains formed a distinct evolutionary lineage within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 34 publications
2
52
0
1
Order By: Relevance
“…Except Arthrobacter alkaliphilus, which shares highest 16S rRNA gene similarity with Arthrobacter methylotrophus (97.4%), these species are grouped in rRNA cluster 3. The peptidoglycan of Arthrobacter albidus and Arthrobacter echigonensis is composed of the amino acids Lys, Ser, and Ala (Ding et al, 2009), which is consistent with a peptidoglycan interpeptide bridge of Lys-Ser-Ala x and placement of these two species in subclade V together with the species of the genus Sinomonas.…”
Section: Species Of Arthrobacter Rrna Cluster 2 (Arthrobacter Aurescesupporting
confidence: 62%
See 1 more Smart Citation
“…Except Arthrobacter alkaliphilus, which shares highest 16S rRNA gene similarity with Arthrobacter methylotrophus (97.4%), these species are grouped in rRNA cluster 3. The peptidoglycan of Arthrobacter albidus and Arthrobacter echigonensis is composed of the amino acids Lys, Ser, and Ala (Ding et al, 2009), which is consistent with a peptidoglycan interpeptide bridge of Lys-Ser-Ala x and placement of these two species in subclade V together with the species of the genus Sinomonas.…”
Section: Species Of Arthrobacter Rrna Cluster 2 (Arthrobacter Aurescesupporting
confidence: 62%
“…For the latter two species only the predominant amino acids of Lys, Ser, Thr, and Ala were reported (Ding et al, 2009). Except Arthrobacter alkaliphilus, which shares highest 16S rRNA gene similarity with Arthrobacter methylotrophus (97.4%), these species are grouped in rRNA cluster 3.…”
Section: Species Of Arthrobacter Rrna Cluster 2 (Arthrobacter Aurescementioning
confidence: 99%
“…This affiliation is in agreement with chemotaxonomic traits of this species, including its quinone system (ubiquinone Q-10 predominant), fatty acid profile (hydroxy fatty acids present, C 18 : 1 and C 19 : 0 cyclo predominant) and a polar lipid profile that suggests the presence of phosphatidylethanolamine (PE), monomethylethanolamine, phosphatidylglycerol (PG), diphosphatidylglycerol (DPG) and phosphatidylcholine (Collins, 1986). Phylogenetic analyses employing the neighbour-joining algorithm and embracing the vast majority of species of the genus Arthrobacter (Ding et al, 2009;Ganzert et al, 2011;Yassin et al, 2011b;Margesin et al, 2012) do not indicate a stable internal structure of the genus. This is indicated by the fact that many branching nodes are not supported by high bootstrap values (.70 %) and numerous nodes were not found with the maximumlikelihood or maximum-parsimony algorithm.…”
Section: Strict Aerobesmentioning
confidence: 99%
“…However, in phylogenetic trees, A. crystallopoietes is usually the sole species on a separate branch ( Fig. 1; Ding et al, 2009;Ganzert et al, 2011;Yassin et al, 2011b;Margesin et al, 2012;Busse et al, 2012). The peptidoglycan structure also does not assign this species clearly to the 'A.…”
Section: Overview Of Groupings Within the Genus Arthrobactermentioning
confidence: 99%
“…Generally, their G + C content of DNA is 59% -70%; the representative species of the genus is Arthrobacter globisformis. Many members of this genus have been isolated from various environments, such as air, oil, fresh water, tobacco leaves, human skin, activated sludge, polluted soil, and so on [2]. With the scientific research progress, it has been shown that functions of this genus can be applied to many fields, which are agriculture, medicine, industry, especially environmental rehabilitation fields, etc.…”
Section: Introductionmentioning
confidence: 99%